Language Acquisition: From Notion to Expression (Global Journal of Human-Social Science, 2013)
This paper discusses language acquisition from a perspective of a dichotomy between the communicative notion and its expression. The communicative notion refers to what the speaker intends to communicate with the person or listener that he wants to address and the expression is the realization of the communicative notion by means of language. The authors first introduced Vygotsky's theory on the relation between thought and language, then discussed the mechanisms of the communicative notion acting as the starting point of language acquisition through the analysis of the description of a child learning to say the word "doll", provided by Bloomfield, and finally explained how expression develops on the basis of the communicative notion.
Keywords: language acquisition; communicative notion; expression.; expression